Analisis Kepentingan Nasional Indonesia Dan Inggris Dalam Kerja Sama Transisi Energi: Studi Kasus Program Menuju Transisi Energi Rendah Karbon Indonesia (MENTARI) - Maruti, Ayu; Chotimah, Hidayat Chusnul; Arisanto, Puguh Toko (Frequency of International Relations (FETRIAN), 2025)
This study aims to examine the national interests of the United Kingdom and Indonesia within the MENTARI program, utilizing Axelrod and Keohane's "Shadow of the Future" dimension as an analytical framework. Authors employ qualitative methods, including interviews and document analysis, The findings indicate a shared recognition by both nations that the global energy landscape will be predominantly shaped by renewable sources. Therefore, both countries established a partnership to speed up the energy transition and reduce their dependence on environmentally harmful fossil fuels, a major driver of climate change. The analysis reveals that the UK's interests align with its obligation as a developed country under the Paris Agreement to provide climate finance, coupled with its strategic ambition to secure a market share in Indonesia's renewable energy sector to bolster its position as a global leader in the field. Conversely, Indonesia's primary interest lies in attracting foreign investment to catalyse its domestic renewable energy development and accelerate its national energy transition process.